Complete axillary node dissection - Carriquiry, Luis A; Borges, Freddy; Levin, Roberto; Mate, Miguel; Priario, julio C (Cirugía del Uruguay, 1984)
Authors discuss their experience with 34 cases of complete extraction of axillar ganglial mass, performed as an isolated operation in the treatment of lymphatic metastasis of a variety of tumors, melanomas in particular. They specially emphasize the importance of certain technical aspects . transverse incision of the skin, careful handling of the anatomy & function of main pectoral muscle, preservation of the indemnity of the nerves of the main serratus and the latssimus dorsi muscle, close and aspirative drainage in order to reduce post-operative morbidity to a mínimum.